2020
DOI: 10.5430/ijhe.v9n2p78
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Work Ethics-Based Organizational Citizenship Behavior to Improve the Job Satisfaction and Organizational Commitment of Higher Education Lecturers in Indonesia

Abstract: Problems of organizational citizenship behavior among academics, especially lecturers, are something relevant in the study of the quality of an organization. The purpose of this study is to analyze the increase in organizational citizenship behavior based on Islamic work ethics, organizational satisfaction and commitment. By collecting data from 365 lecturers from 14 private universities as sample in the city of Bandung, the sampling was taken with proportional random sampling techniques. Data analysis techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
3
26
0
3
Order By: Relevance
“…Based on the data analysis that has been done, it can be concluded that the emotional intelligence variable affects students' ethical behavior. The results of this study support previous research [12][13], [14] shows that emotional intelligence has a significant positive effect on student ethical behavior. 2.…”
Section: The Partial Test Results Show That the Independent Variablesupporting
confidence: 91%
“…Based on the data analysis that has been done, it can be concluded that the emotional intelligence variable affects students' ethical behavior. The results of this study support previous research [12][13], [14] shows that emotional intelligence has a significant positive effect on student ethical behavior. 2.…”
Section: The Partial Test Results Show That the Independent Variablesupporting
confidence: 91%
“…Hypothesis 4 (H4) : estimated strandardized regression weight coefficient between the organization's commitment variable to organizational citizenship behavior of 0.432 and the value of P value indicates a probability of 0.000 smaller than 0.05, this indicates that the higher the commitment of the organization, the higher the organizational citizenship behavior of the Lecturers. So it can be concluded that hypothesis 4 is accepted, the results of this study are in line with previous research [3], [26] that demonstrates the influence of organizational commitment to organizational citizenship behavior. 5.…”
Section: Hypothesis 1 (H1) : Estimated Strandardized Regression Weighsupporting
confidence: 91%
“…Lecturers are an asset owned by educational institutions to develop programs to educate the lives of the nation that during the covid-19 pandemic must be able to adapt to technological developments to support the implementation of tridharma universities both education and teaching, research and community service [1]. Problems related to improving the quality of education where it will require resources that have good competence, this leads to extra hole as a lecturer such as willingness to help fellow lecturers [2], willingly do extra work, try to avoid conflicts between colleagues, and respect the rules in the organization [3]. An extra behavior in work or commonly called organizational citizenship behavior, this behavior is an action that is not a formal requirement for employees but can increase effectiveness in functions within an organization [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to Moekijat (2002), the main objective of applying discipline to employees is to maximize their work results by reducing the waste of time and energy. In addition, the application of behavior is to prevent damage or loss of company assets, as well as avoid accidents due to the carelessness of employees, while carrying out work tasks (Romi & Ahman, 2020). The application of discipline aims to condition the behavior of respecting work time, and to resolve differences of opinion among employees and prevent disobedience that causes conflicts in the work environment.…”
Section: Supervision Discipline and Work Climatementioning
confidence: 99%